VIRTUAL SERVICE OF UNIVERSITY LIBRARY – NEW FORM OF REFERENCE SERVIVE - Kovalova, Zoia F. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This paper examines new forms of reference service, including virtual service of university library.